African Seed Enterprises Sowing the Seeds of Food Security - Mele, Paul Van (CABI, 2014)
The subject of seed provision commands an exceptional amount of attention in most discussions of agricultural development. The reasons are not difficult to understand, as the security and quality of seed supply are among the principal determinants of any farmer’s success. But, despite this unanimity of interest, there is relatively little agree- ment on what needs to be done to support the growth of effective and equitable seed provision in developing countries. Part of the controversy over seed provision is the product of legitimate concerns about the nature and impact of the commercial seed sector. There is, for instance, the danger that an overemphasis on commercial seed supply will disregard the role that farmers continue to play in the identification and preservation of productive germ- plasm, the maintenance of local systems of seed sale and exchange, and innovations in crop management. In addition, there are understandable worries about the growing reach of the multinational ‘life sciences’ industry, its increasing control of the seed sec- tor and the concentration of access to technology in too few hands. But commercial seed supply can take many different forms, and it is a larger part of many ‘traditional’ farming systems than people may realize. It is difficult to imagine a productive agricultural system in the 21st century without access to some type of formal seed provision through various types of seed enterprise. As agricultural econo- mies develop there is a natural shift towards specialization in the supply of products and services that were previously part of self-sufficient farms or communities. The access to commercial seed supply offers wider access to the products of modern plant breeding and helps ensure that a farmer’s seed supply is not completely dependent on the vagaries of local climate or other uncertainties in local production systems. In addi- tion, the expansion of agricultural markets often provides farmers with an opportunity to earn a premium for the specific qualities of their produce, which may require more attention to high quality and uniform seed than can be provided on-farm. The avail- ability of commercial seed also allows the farmer to invest time in other activities, on- or off-farm, without having to worry about next year’s seed supply.